Inhibition Effect Extract Stolephorus Insularis As A Antimicroba In Staphylococcus aereus Bacteria - Ayulistya Paramita Sutarto; Yulie Emilda Akhwan (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2018)
Background: Untreated caries will continue and microorganisms enter the pulp resulting in an inflammatory response and pulp necrosis. Sterilization is one part of root canal treatment and is important for the success of root canal treatment. Stolephorus insularis contains antibacterial substances such as fluor. Previous research showed that extract Stolephorus insularis has antibacterial activity in Streptococcus mutans bacteria. Purpose: This study aims to determine the antibacterial power of Stolephorus insularis extract on the growth of Staphylococcus aereus bacteria by using 3 concentrations of 18%, 24% and 30%. Material and Method: This resesarch use culture of Staphylococcus aereus bacteria in MH blood agar, Stolephorus insularis extract with various concentrations (18%, 24%, 30%), 7% Na CMC, 1% DMSO solution, agar BHI media. Culture of Staphylococcus aereus was taken from liquid BHI media, then rubbed on the entire surface of BHI media using a sterile cotton stick. The antibacterial zone formed is measured. Result: Based on the results of the Mann-Whitney test there were significant differences in the inhibitory power of Staphylococcus aureus bacteria (p <0.05) in the K + group with groups K-, P1, P2 and P3. Whereas between groups P1 with K-, group P2 with K- and P1, and group P3 with K-, P1 and P2 there were no significant differences because the significant value was greater than 0.05. Conclusion: There is no antimicrobial power at concentrations of 18%, 24%, and 30%. Quantitative research needs to be done to determine the decrease in the number of bacterial colonies.